(untitled) (World Bulletin of Public Health, 2023)
Lacunar strokes, characterized by small infarctions in the deep brain structures, represent a significant subtype of ischemic stroke. Accurate diagnosis and appropriate management strategies are essential for optimizing patient outcomes. This review article provides a comprehensive overview of the diagnosis and management of lacunar strokes, highlighting key findings and emerging trends in the field. This review article provides valuable insights into the diagnosis and management of lacunar strokes. It emphasizes the importance of accurate diagnosis, risk factor management, antiplatelet therapy, rehabilitation, and emerging treatment strategies. By implementing comprehensive and tailored approaches, healthcare professionals can optimize patient care, reduce recurrence rates, and improve functional outcomes in individuals affected by lacunar strokes. Continued research and advancements in the field hold promise for further enhancing the diagnosis, treatment, and long-term outcomes of lacunar strokes.